2014
DOI: 10.1021/am500685k
|View full text |Cite
|
Sign up to set email alerts
|

Cocoon-in-Web-Like Superhydrophobic Aerogels from Hydrophilic Polyurea and Use in Environmental Remediation

Abstract: Polyurea (PUA) develops H-bonding with water and is inherently hydrophilic. The water contact angle on smooth dense PUA derived from an aliphatic triisocyanate and water was measured at θ=69.1±0.2°. Nevertheless, texture-related superhydrophobic PUA aerogels (θ'=150.2°) were prepared from the same monomer in one step with no additives, templates, or surfactants via sol-gel polymerization carried out in polar, weakly H-bonding acetonitrile. Those materials display a unique nanostructure consisting of micrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 53 publications
5
77
0
1
Order By: Relevance
“…Interestingly,f or the higher NP concentrations,the shape of the frozen colloid resembles the shape of the resulting aerogel ( Figure 2C). Therefore,o ur new cryogelation method is advantageous in comparison to conventional aerogels (and xerogels) resulting from lyogelated gels,w hich are frequently accompanied by syneresis [2,4,7,11,21,22] (i.e.t he gels are usually smaller than the colloid liquid). Therefore,o ur new cryogelation method is advantageous in comparison to conventional aerogels (and xerogels) resulting from lyogelated gels,w hich are frequently accompanied by syneresis [2,4,7,11,21,22] (i.e.t he gels are usually smaller than the colloid liquid).…”
supporting
confidence: 70%
“…Interestingly,f or the higher NP concentrations,the shape of the frozen colloid resembles the shape of the resulting aerogel ( Figure 2C). Therefore,o ur new cryogelation method is advantageous in comparison to conventional aerogels (and xerogels) resulting from lyogelated gels,w hich are frequently accompanied by syneresis [2,4,7,11,21,22] (i.e.t he gels are usually smaller than the colloid liquid). Therefore,o ur new cryogelation method is advantageous in comparison to conventional aerogels (and xerogels) resulting from lyogelated gels,w hich are frequently accompanied by syneresis [2,4,7,11,21,22] (i.e.t he gels are usually smaller than the colloid liquid).…”
supporting
confidence: 70%
“…polyurea [144], polyimides [145], polyamide [146], polyacrylonitriles [127], polyurethanes [147], polystyrene [148], polybenzoxazine [149], poly(dicyclopentadiene) [150], etc.…”
Section: Organic Aerogelsmentioning
confidence: 99%
“…On the other hand, some industrial applications of aerogels [158] demanded highly flexibility and foldability, which cannot be attainable by the polymer-cross-linked silica aerogels. Leventis et al reported the synthesis of a highly flexible aerogel from polyurea and poly urethane [144,159,160]. They concluded that macroscopic flexibility is indirectly correlated with the molecular properties of the monomer.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[1][2][3][4] Over the past years, most of the research works focused on the silica and metal-oxide aerogels. [5][6][7][8] Recently, a variety of new aerogels have been synthesized, such as organic polymer-based aerogels, [9][10][11][12] supramolecular aerogels, [13][14][15] hybrid aerogels, 16,17 and graphene aerogels. 18,19 Organic polymerbased aerogels including polyaimide, 20 polyurethane, 21 and cellulose aerogels 22,23 have attracted increasing interests due to their outstanding mechanical properties.…”
Section: Introductionmentioning
confidence: 99%